POPCOM @ 46 and beyond (1969-2015) working towards healthy, happy, and empowered Filipino families. (Commission on Population, 2016)
This book is dedicated to and a celebration of all the people behind POPCOM in our advocacy to heighten support and participation in the implementation of the Philippine Population Management Program (PPMP), and the hope and encouragement they bring to the people in attaining well-planned, healthy, happy, prosperous, and empowered Filipino families.